Electronic signatures : - Schellekens, Maurice (T.M.C. Asser Press, 2004)
The contention that the provision of European Directives on functional legal requirements for digital signature validity solves a core problem of electronic commerce can at best be called naive. In this book it is made clear that there are no simple shortcuts for the lawyer who is concerned with authenticated digital transactions. Schellekens describes the main aspects of authentication technologies, presenting the technical insights needed to get to the legal semantics of functional equivalence between traditional and digital signatures. He focuses on the usability of authentication technology and what it entails for its users. The research for this book is based on an in-depth literature study and interviews with highly qualified experts in the field. It provides valuable tools and background information not only for everyone active in or setting out on e-business in its widest concept, but also for practising lawyers and students of information technology.